Positive electrode active material and preparation method thereof, secondary battery, battery module, battery pack and electric device
By covering the high-nickel positive electrode active material with zirconium-based oxygen ion conductor and fast ion conductor, the problem of poor material structure stability is solved, and the circulation and safety performance of lithium-ion secondary batteries are significantly improved.
Patent Information
- Application Number
- CN202210059936.6
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2022-01-19
- Publication Date
- 2025-02-07
- Estimated Expiration
- 2042-01-19
AI Technical Summary
The existing positive electrode active materials have poor structural stability under high nickel content, resulting in a decrease in the capacity of lithium-ion secondary batteries and a poor circulation performance.
LiNixCoyAzO2 is used as the core, and the cladding layer includes a zirconium-based oxygen ion conductor as the first cladding layer and a fast ion conductor LiM2 (PO4)3 as the second cladding layer, thereby improving the cyclic performance of the positive electrode active material through this structure.
It effectively inhibits the production of gas in the charge and discharge cycle of positive electrode active materials, improves its circulation and safety performance, while maintaining dynamic performance.
Smart Images

Figure CN115842113B_ABST
Abstract
Description
Technical Field
[0001] The present application relates to the technical field of lithium secondary batteries, and in particular to a positive electrode active material and a preparation method thereof, a secondary battery, a battery module, a battery pack and an electrical device. Background Art
[0002] In recent years, as the application scope of lithium-ion secondary batteries has become more and more extensive, lithium-ion batteries have been widely used in energy storage power systems such as hydropower, thermal power, wind power and solar power stations, as well as power tools, electric bicycles, electric motorcycles, electric vehicles, military equipment, aerospace and other fields. As lithium-ion secondary batteries have made great progress, higher requirements have been put forward for their energy density, cycle performance and safety performance. In addition, as the choice of positive electrode active materials has become increasingly limited, high-nickel positive electrode active materials are considered to be the best choice to meet the requirements of high energy density.
[0003] However, as the nickel content continues to increase, its structural stability becomes worse and worse. Improving the rate performance and cycle performance of materials by coating or doping is currently a relatively effective means, but the existing methods will cause varying degrees of damage to the performance of lithium-ion batteries, for example, the gram capacity of lithium-ion batteries is reduced, the cycle performance is deteriorated, etc. Therefore, the existing coated or doped positive electrode materials still need to be improved. Summary of the invention
[0004] Technical problem to be solved by the invention
[0005] The present application is made in view of the above-mentioned problems, and its purpose is to provide a positive electrode active material with LiNi x Co y A z O2 is the core, and the coating layer includes an oxygen ion conductor as a first coating layer and a fast ion conductor as a second coating layer, thereby improving the cycle performance of the positive electrode active material while suppressing the gas generation of the positive electrode active material.
[0006] Technical solutions to solve problems
[0007] In order to achieve the above-mentioned objectives, the present application provides a positive electrode active material and a preparation method thereof, a secondary battery, a battery module, a battery pack and an electrical device.
[0008] The first aspect of the present application provides a positive electrode active material, comprising a core, a first coating layer and a second coating layer, wherein the first coating layer is coated on the surface of the core, and the second coating layer is coated on the surface of the first coating layer, wherein the core is LiNi x Co y A zO2, wherein A is Mn or Al, 0.6≤x<1, 0<y≤0.2, x+y+z=1, and the first coating layer is Ln x Zr 1-x O 2-δ , 0.08<x<0.2, 0.04<δ<0.1, wherein Ln is selected from one or more of Gd, Dy, Er, Yb, Y, the second coating layer is LiM2(PO4)3, wherein M is Ti or Zr, relative to the total weight of the positive electrode active material, the weight proportion of the first coating layer is set to A%, the thickness of the first coating layer is set to d1, unit: nm, the thickness of the second coating layer is set to d2, unit: nm, the positive electrode active material satisfies the following conditions: 0<d1 / (d1+d2+A)≤0.83, optionally, 0.3≤d1 / (d1+d2+A)≤0.6.
[0009] Therefore, the present application coats zirconium-based oxygen ion conductors and fast ion conductors on the surface of high-nickel ternary positive electrode active material particles. The oxygen atoms of the zirconium-based oxygen ion conductor have a strong and good complexing ability, which suppresses the oxygen generated by the irreversible reaction on the surface of the positive electrode active material particles during the charge and discharge cycle and the heat generated by the side reaction between the electrolyte, thereby improving the thermal runaway of the positive electrode active material. In addition, the zirconium element of the zirconium-based oxygen ion conductor can form a Zr-O bond with the oxygen element in the core material during the sintering process, thereby improving the lattice stability of the positive electrode active material and thus improving its cycle performance. The fast ion conductor has good stability and good transmission capacity for lithium ions. Therefore, the introduction of the fast ion conductor can improve the kinetic properties of the positive electrode active material particles. At the same time, when the thickness of the first coating layer, i.e., d1, the thickness of the second coating layer, i.e., d2, and the weight proportion of the first coating layer, A%, satisfy the above relationship, the coating layer can suppress gas production while not affecting the kinetic properties of the positive electrode active material, thereby improving the cycle performance of the positive electrode active material.
[0010] In any embodiment, the thickness of the first coating layer, ie, d1 = 2-35 nm, and / or the thickness of the second coating layer, ie, d2 = 2-35 nm.
[0011] Therefore, when the first coating layer and the second coating layer are within the above range, the coating layer is uniformly coated on the surface of the core of the high-nickel ternary positive electrode active material, thereby inhibiting the gas production of the positive electrode active material during the charging and discharging process, and improving its cycle performance.
[0012] In any embodiment, the weight proportion of the first coating layer is A% of 0.2-5% relative to the total weight of the positive electrode active material, and / or the weight proportion of the second coating layer is 0.2-5% relative to the total weight of the positive electrode active material.
[0013] Therefore, from the perspective of suppressing the gas production of the positive electrode active material while improving the lithium ion transmission capacity of the positive electrode active material, the weight ratio of the first coating layer and the second coating layer is selected to be within the above range. When the weight ratio of the first coating layer and the second coating layer is within the above range, the following situations can be avoided: since the zirconium-based oxygen ion conductor of the first coating layer has no electrochemical activity to lithium ions, if the content of the first coating layer is too high, it will affect the kinetic properties of the positive electrode active material and hinder the insertion and extraction of lithium ions; in addition, if the content of the second coating layer is too high, the content of the first coating layer is insufficient, which may weaken the effect of the oxygen ion conductor in suppressing the gas production of the positive electrode active material, resulting in the lattice structure of the high-nickel ternary positive electrode active material may also collapse during the charge and discharge cycle, affecting its cycle performance.
[0014] In any embodiment, the positive electrode active material Dv50=5-20 μm. Therefore, from the perspective of facilitating the preparation of the positive electrode slurry, the Dv50 of the positive electrode active material is selected to be within the above range.
[0015] The second aspect of the present application also provides a method for preparing a positive electrode active material, comprising:
[0016] Step a: Precursor containing Zr element, precursor containing Ln element and LiNi x Co y A z O2 is added to deionized water, stirred at 60-80°C until the water is completely evaporated, and continued to dry for 4-6 hours to obtain material A, wherein A is Mn or Al, 0.6≤x<1,0<y≤0.2, x+y+z=1, and the Ln element is selected from one or more of Gd, Dy, Er, Yb, and Y.
[0017] Step b: After crushing material A, place it in an oxidizing atmosphere and sinter it at 650-950°C for 2-6 hours to obtain material B.
[0018] Step c: dissolving lithium phosphate, a precursor containing an element M, and a complexing agent in a solvent, and then adding material B, stirring at 60-80° C. until the solvent is completely evaporated, and continuing to dry for 4-6 hours to obtain material C, wherein M is Ti or Zr,
[0019] Step d: After material C is crushed, it is placed in an oxidizing atmosphere, first sintered at 150-250° C. for 5-10 hours, and then heated to 550-750° C. and continued to sinter for 5-15 hours to obtain a positive electrode active material.
[0020] Thus, the coating layer of the positive electrode active material prepared by the above method includes a zirconium-based oxygen ion conductor and a fast ion conductor. The oxygen atoms in the zirconium-based oxygen ion conductor have a strong and good complexing ability, which inhibits the oxygen generated by the irreversible reaction on the surface of the positive electrode active material particles during the charge and discharge cycle and the heat generated by the side reaction with the electrolyte, thereby improving the thermal runaway of the positive electrode active material. In addition, the zirconium element of the zirconium-based oxygen ion conductor can form a Zr-O bond with the oxygen element in the core material during the sintering process, thereby improving the lattice stability of the positive electrode active material and thus improving its cycle performance. Due to the good stability of the fast ion conductor, it has a good transmission ability for lithium ions, thereby improving the kinetic properties of the positive electrode active material.
[0021] In any embodiment, in step a, the molar ratio of the Zr element precursor to the Ln element precursor is (4-12): 1, and / or the sum of the weights of the Zr element precursor and the Ln element precursor relative to the LiNi x Co y A z The weight of O2 is the sum of the weight of the precursor containing Zr and the precursor containing Ln: LiNi x Co y A z The weight of O2 is (0.2-10):100.
[0022] Therefore, LiNi x Co y A z The surface of O2 is uniformly coated with a layer of zirconium-based oxygen ion conductor, thereby improving the LiNi x Co y A z The problem of O2 producing gas during the circulation process.
[0023] In any embodiment, in step c, the weight ratio of lithium phosphate salt to the precursor containing element M is (0.5-3):1, and / or the molar ratio of lithium phosphate salt to complexing agent is 1:(0.6-2), and / or the sum of the weight of lithium phosphate salt and the precursor containing element M relative to the weight of material B, i.e. (the sum of the weight of lithium phosphate salt and the precursor containing element M): the weight of material B is (0.05-9):100.
[0024] As a result, the surface of the positive electrode active material is uniformly coated with a layer of LiM2(PO4)3 fast ion conductor, thereby improving the cycle performance of the positive electrode active material.
[0025] In any embodiment, in step a, the Zr element-containing precursor is selected from one or more of Zr(NO3)4, H2N2O7Zr, ZrOCl2, ZrOCl, and ZrO2, and the Ln element-containing precursor is selected from one or more of Gd element precursor, Dy element precursor, Er element precursor, Yb element precursor, Y element-containing precursor, and Ti element precursor.
[0026] Therefore, from the perspective of the stability of the synthesized zirconium-based oxygen ion conductor, the above-mentioned precursor containing the Zr element and the precursor containing the Ln element are selected.
[0027] In any embodiment, the Gd-containing element precursor is selected from Gd(NO3)4·6H2O, C6H 11 One or more of GdO7, and / or, the Dy element precursor is selected from Dy(NO3)4·6H2O, C6H 17 DYNAMIC 10 One or more of, and / or, the Er-containing element precursor is selected from Er(NO3)3·5H2O, C2H 11 One or more of ErO6, and / or, the precursor containing Yb element is selected from Yb(NO3)3·5H2O, and / or, the precursor containing Y element is selected from Y(NO3)3·6H2O, C6H 17 O 10 One or more of Y, Y2O3, and / or the Ti-containing element precursor is selected from one or more of TiCl4, TiOSO4, TiSO4, and tetrabutyl orthotitanate.
[0028] Therefore, from the perspective of synthesizing a zirconium-based oxygen ion conductor with good complexing ability for oxygen atoms, the above-mentioned Gd element precursor, Dy element precursor, Er element precursor, Yb element precursor, Y element precursor and Ti element precursor are selected.
[0029] In any embodiment, in step c, the lithium phosphate salt is selected from one or more of lithium phosphate and lithium dihydrogen phosphate, and / or the complexing agent is selected from one or more of oxalic acid and citric acid, and / or the solvent is selected from one or more of anhydrous ethanol, ethylene glycol, methanol or N-methylpyrrolidone. Therefore, from the perspective of synthesizing a fast ion conductor of LiM2(PO4)3 with uniform composition and good performance, the above-mentioned lithium phosphate salt, complexing agent and solvent are selected.
[0030] In any embodiment, in step b, the oxidizing atmosphere is oxygen or air.
[0031] Therefore, when the above-mentioned oxidizing atmosphere is selected, the coating layer has a complete lattice and has a good complexing ability for oxygen atoms, thereby inhibiting the gas generation of the positive electrode active material during the charge and discharge cycle.
[0032] A third aspect of the present application provides a secondary battery, comprising the positive electrode active material of the first aspect of the present application or the positive electrode active material prepared according to the method of the second aspect of the present application.
[0033] A fourth aspect of the present application provides a battery module, comprising the secondary battery of the third aspect of the present application.
[0034] A fifth aspect of the present application provides a battery pack comprising the battery module of the fourth aspect of the present application.
[0035] The sixth aspect of the present application provides an electrical device comprising at least one selected from the secondary battery of the third aspect of the present application, the battery module of the fourth aspect of the present application, or the battery pack of the fifth aspect of the present application.
[0036] Effects of the Invention
[0037] The present application provides a positive electrode active material, LiNi x Co y A z O2 is the core, and the coating layer includes an oxygen ion conductor as the first coating layer Ln x Zr 1-x O 2-δ , and the fast ion conductor LiM2(PO4)3 is used as the second coating layer. Zirconium-based oxygen ion conductors have a strong and good complexing ability for oxygen atoms, which inhibits the oxygen generated by the irreversible reaction on the surface of the positive electrode active material particles during the charge and discharge cycle, as well as the heat generated by the side reaction between the electrolyte, thereby improving the thermal runaway of the positive electrode active material. In addition, the zirconium element of the zirconium-based oxygen ion conductor can form a Zr-O bond with the oxygen element in the core material during the sintering process, which improves the lattice stability of the positive electrode active material and thus improves its cycle performance. Due to the good stability of the fast ion conductor, it has a good transmission ability for lithium ions, thereby improving the kinetic properties of the positive electrode active material. BRIEF DESCRIPTION OF THE DRAWINGS
[0038] Figure 1 is a schematic diagram of a secondary battery according to one embodiment of the present application.
[0039] Figure 2 yes Figure 1 An exploded view of a secondary battery according to an embodiment of the present application is shown.
[0040] Figure 3 is a schematic diagram of a battery module according to an embodiment of the present application.
[0041] Figure 4 It is a schematic diagram of a battery pack according to one embodiment of the present application.
[0042] Figure 5 yes Figure 4 An exploded view of a battery pack according to an embodiment of the present application is shown.
[0043] Figure 6 Schematic diagram of an electrical device using a secondary battery according to an embodiment of the present application as a power source.
[0044] Description of reference numerals:
[0045] 1 battery pack; 2 upper box; 3 lower box; 4 battery module; 5 secondary battery; 51 shell; 52 electrode assembly; 53 top cover assembly. DETAILED DESCRIPTION
[0046] Below, the embodiments of the positive electrode active material and its manufacturing method, secondary battery, battery module, battery pack and electrical device of the present application are specifically disclosed with appropriate reference to the drawings. However, there are cases where unnecessary detailed descriptions are omitted. For example, there are cases where detailed descriptions of well-known matters and repeated descriptions of actually the same structure are omitted. This is to avoid the following description from becoming unnecessarily lengthy and to facilitate the understanding of those skilled in the art. In addition, the drawings and the following descriptions are provided for those skilled in the art to fully understand the present application and are not intended to limit the subject matter described in the claims.
[0047] "Scope" disclosed in the present application is limited in the form of lower limit and upper limit, and a given range is limited by selecting a lower limit and an upper limit, and the selected lower limit and upper limit define the boundary of a special range. The scope limited in this way can be including end values or not including end values, and can be arbitrarily combined, that is, any lower limit can be combined with any upper limit to form a scope. For example, if the scope of 60-120 and 80-110 is listed for a specific parameter, it is understood that the scope of 60-110 and 80-120 is also expected. In addition, if the minimum range values 1 and 2 are listed, and if the maximum range values 3, 4 and 5 are listed, the following scope can be all expected: 1-3, 1-4, 1-5, 2-3, 2-4 and 2-5. In the present application, unless otherwise specified, the numerical range "ab" represents the abbreviation of any real number combination between a and b, wherein a and b are real numbers. For example, the numerical range "0-5" means that all real numbers between "0-5" are listed in this document, and "0-5" is just an abbreviation of these numerical combinations. In addition, when a parameter is expressed as an integer ≥ 2, it is equivalent to disclosing that the parameter is, for example, an integer of 2, 3, 4, 5, 6, 7, 8, 9, 10, 11, 12, etc.
[0048] If not otherwise specified, all embodiments and optional embodiments of the present application can be combined with each other to form a new technical solution.
[0049] Unless otherwise specified, all technical features and optional technical features of this application can be combined with each other to form a new technical solution.
[0050] If there is no special explanation, all steps of the present application can be performed sequentially or randomly, preferably sequentially. For example, the method includes steps (a) and (b), which means that the method may include steps (a) and (b) performed sequentially, or may include steps (b) and (a) performed sequentially. For example, the method may further include step (c), which means that step (c) may be added to the method in any order. For example, the method may include steps (a), (b) and (c), or may include steps (a), (c) and (b), or may include steps (c), (a) and (b), etc.
[0051] If there is no special explanation, the "include" and "comprising" mentioned in this application represent open-ended or closed-ended expressions. For example, the "include" and "comprising" may represent that other components not listed may also be included or only the listed components may be included or only the listed components may be included.
[0052] If not specifically stated, in this application, the term "or" is inclusive. For example, the phrase "A or B" means "A, B, or both A and B". More specifically, any of the following conditions satisfies the condition "A or B": A is true (or exists) and B is false (or does not exist); A is false (or does not exist) and B is true (or exists); or both A and B are true (or exist).
[0053] Positive electrode active material
[0054] In one embodiment of the present application, a positive electrode active material is proposed, including a core, a first coating layer and a second coating layer, wherein the first coating layer is coated on the surface of the core, and the second coating layer is coated on the surface of the first coating layer, wherein the core is LiNi x Co y A z O2, where A is Mn or Al, 0.6≤x<1, 0<y≤0.2, x+y+z=1, and the first coating layer is Ln x Zr 1- x O 2-δ, 0.08<x<0.2, 0.04<δ<0.1, wherein Ln is selected from one or more of Gd, Dy, Er, Yb, Y, the second coating layer is LiM2(PO4)3, wherein M is Ti or Zr, relative to the total weight of the positive electrode active material, the weight proportion of the first coating layer is set to A%, the thickness of the first coating layer is set to d1, unit: nm, the thickness of the second coating layer is set to d2, unit: nm, the positive electrode active material satisfies the following conditions: 0<d1 / (d1+d2+A)≤0.83, optionally, 0.3≤d1 / (d1+d2+A)≤0.6.
[0055] Although the mechanism is not yet clear, the applicant has unexpectedly discovered through a large number of experiments that coating the surface of high-nickel ternary positive electrode active material particles with zirconium-based oxygen ion conductors and fast ion conductors can improve their safety and cycle performance. Zirconium-based oxygen ion conductors have a strong and good complexing ability for oxygen atoms, which inhibits the oxygen generated by irreversible reactions on the surface of the positive electrode active material particles during the charge and discharge cycle and the heat generated by side reactions with the electrolyte, thereby improving the thermal runaway of the positive electrode active material and improving the safety performance of secondary batteries using the positive electrode active material. In addition, the zirconium element in the zirconium-based oxygen ion conductor can form a Zr-O bond with the oxygen element in the core material during the sintering process, which improves the lattice stability of the positive electrode active material and thereby improves its cycle performance. Fast ion conductors have good stability and good transmission capabilities for lithium ions. Therefore, by introducing fast ion conductors, the kinetic properties of the positive electrode active material particles can be improved. At the same time, when the thickness of the first coating layer, i.e., d1, the thickness of the second coating layer, i.e., d2, and the weight proportion of the first coating layer, A%, satisfy the above relationship, it is possible to suppress gas production without affecting the kinetic properties of the positive electrode active material, thereby improving the cycle performance of the positive electrode active material.
[0056] In some embodiments, the thickness of the first coating layer, ie, d1, is 2-35 nm, and / or the thickness of the second coating layer, ie, d2, is 2-35 nm.
[0057] Therefore, when the first coating layer and the second coating layer are within the above range, the coating layer can be evenly coated on the surface of the core of the high-nickel ternary positive electrode active material, thereby inhibiting its gas production during the charging and discharging process, increasing the diffusion rate of lithium ions in the particles, and improving its cycle performance.
[0058] In some embodiments, the weight ratio of the first coating layer is A%=0.2-5% relative to the total weight of the positive electrode active material, and / or the weight ratio of the second coating layer is 0.2-5% relative to the total weight of the positive electrode active material.
[0059] Therefore, from the perspective of suppressing the gas production of the positive electrode active material while improving the lithium ion transmission capacity of the positive electrode active material, the weight ratio of the first coating layer and the second coating layer is selected to be within the above range. When the weight ratio of the first coating layer and the second coating layer is within the above range, the following situations can be avoided: since the zirconium-based oxygen ion conductor of the first coating layer has no electrochemical activity to lithium ions, if the content of the first coating layer is too high, it may affect the kinetic properties of the positive electrode active material and hinder the insertion and extraction of lithium ions; if the content of the second coating layer is too high, the content of the first coating layer is insufficient, which may weaken the effect of the oxygen ion conductor in suppressing the gas production of the positive electrode active material, resulting in the collapse of the lattice structure of the high-nickel ternary positive electrode active material during the charge and discharge cycle, affecting its cycle performance.
[0060] In some embodiments, the positive electrode active material has a Dv50 of 5-20 μm. Therefore, from the perspective of facilitating the preparation of the positive electrode slurry, the Dv50 of the positive electrode active material is selected to be within the above range.
[0061] Method for preparing positive electrode active material
[0062] The embodiment of the present application also provides a method for preparing a positive electrode active material, comprising:
[0063] Step a: Precursor containing Zr element, precursor containing Ln element and LiNi x Co y A z O2 is added to deionized water, stirred at 60-80°C until the water is completely evaporated, and continued to dry for 4-6 hours to obtain material A, wherein A is Mn or Al, 0.6≤x<1,0<y≤0.2, x+y+z=1, and the Ln element is selected from one or more of Gd, Dy, Er, Yb, and Y.
[0064] Step b: After crushing material A, place it in an oxidizing atmosphere and sinter it at 650-950°C for 2-6 hours to obtain material B.
[0065] Step c: dissolving lithium phosphate, a precursor containing an element M, and a complexing agent in a solvent, and then adding material B, stirring at 60-80° C. until the solvent is completely evaporated, and continuing to dry for 4-6 hours to obtain material C, wherein M is Ti or Zr,
[0066] Step d: After material C is crushed, it is placed in an oxidizing atmosphere, first sintered at 150-250° C. for 5-10 hours, and then heated to 550-750° C. and continued to sinter for 5-15 hours to obtain a positive electrode active material.
[0067] Thus, the coating layer of the positive electrode active material prepared by the above method includes a zirconium-based oxygen ion conductor and a fast ion conductor. The oxygen atoms of the zirconium-based oxygen ion conductor have good complexing ability, which inhibits the oxygen generated by the irreversible reaction on the surface of the positive electrode active material particles during the charge and discharge cycle and the heat generated by the side reaction between the electrolyte, thereby improving the thermal runaway of the positive electrode active material. In addition, the zirconium element of the zirconium-based oxygen ion conductor can form a Zr-O bond with the oxygen element in the core material during the sintering process, thereby improving the lattice stability of the positive electrode active material and thus improving its cycle performance. Due to the good stability of the fast ion conductor, it has a good transmission ability for lithium ions, thereby improving the kinetic properties of the positive electrode active material.
[0068] In some embodiments, in step a, the molar ratio of the Zr element precursor to the Ln element precursor is (4-12): 1, and / or the sum of the weights of the Zr element precursor and the Ln element precursor relative to the LiNi x Co y A z The weight of O2 is the sum of the weight of the precursor containing Zr and the precursor containing Ln: LiNi x Co y A z The weight of O2 is (0.2-10):100. Therefore, LiNi x Co y A z The surface of O2 is uniformly coated with a layer of zirconium-based oxygen ion conductor, thereby improving the LiNi x Co y A z The problem of O2 producing gas during the circulation process.
[0069] In some embodiments, in step c, the weight ratio of lithium phosphate salt to the precursor containing the M element is (0.5-3):1, and / or the molar ratio of lithium phosphate salt to the complexing agent is 1:(0.6-2), and / or the sum of the weights of the lithium phosphate salt and the precursor containing the M element relative to the weight of material B (i.e. the sum of the weights of the lithium phosphate salt and the precursor containing the M element): the weight of material B is (0.05-9):100.
[0070] As a result, the surface of the positive electrode active material is uniformly coated with a layer of LiM2(PO4)3 fast ion conductor, thereby improving the cycle performance of the positive electrode active material.
[0071] In some embodiments, in step a, the Zr element-containing precursor is selected from one or more of Zr(NO3)4, H2N2O7Zr, ZrOCl2, ZrOCl, and ZrO2, and the Ln element-containing precursor is selected from one or more of Gd element precursor, Dy element precursor, Er element precursor, Yb element precursor, Y element-containing precursor, and Ti element precursor.
[0072] Therefore, from the perspective of the stability of the zirconium-based oxygen ion conductor, the above-mentioned precursor containing the Zr element and the precursor containing the Ln element are selected.
[0073] In some embodiments, the Gd-containing element precursor is selected from Gd(NO3)4·6H2O, C6H 11 One or more of GdO7, and / or, the Dy element precursor is selected from Dy(NO3)4·6H2O, C6H 17 DYNAMIC 10 One or more of, and / or, the Er-containing element precursor is selected from Er(NO3)3·5H2O, C2H 11 One or more of ErO6, and / or, the precursor containing Yb element is selected from Yb(NO3)3·5H2O, and / or, the precursor containing Y element is selected from Y(NO3)3·6H2O, C6H 17 O 10 One or more of Y, Y2O3, and / or the Ti-containing element precursor is selected from one or more of TiCl4, TiOSO4, TiSO4, and tetrabutyl orthotitanate.
[0074] Therefore, from the perspective of synthesizing a zirconium-based oxygen ion conductor with good complexing ability for oxygen atoms, the above-mentioned Gd element precursor, Dy element precursor, Er element precursor, Yb element precursor, Y element precursor and Ti element precursor are selected.
[0075] In some embodiments, in step c, the lithium phosphate salt is selected from one or more of lithium phosphate and lithium dihydrogen phosphate, and / or the complexing agent is selected from one or more of oxalic acid and citric acid, and / or the solvent is selected from one or more of anhydrous ethanol, ethylene glycol, methanol or N-methylpyrrolidone.
[0076] Therefore, from the perspective of synthesizing a fast ion conductor of LiM2(PO4)3 with uniform composition and good lithium ion transmission ability, the above-mentioned lithium phosphate salt, complexing agent and solvent are selected.
[0077] In some embodiments, in step b, the oxidizing atmosphere is oxygen or air.
[0078] Therefore, when the above-mentioned oxidizing atmosphere is selected, the coating layer has a complete lattice and has good complexing properties for oxygen atoms.
[0079] In addition, the average volume distribution particle size Dv50 refers to the particle size corresponding to the cumulative volume distribution percentage of the positive electrode active material reaching 50%. The average volume distribution particle size Dv90 refers to the particle size corresponding to the cumulative volume distribution percentage of the positive electrode active material reaching 90%. In the present application, the volume average particle sizes Dv50 and Dv90 of the positive electrode active material can be measured by laser diffraction particle size analysis. For example, with reference to the standard GB / T 19077-2016, a laser particle size analyzer (such as MalvernMaster Size 3000) is used for measurement.
[0080] In addition, the secondary battery, battery module, battery pack, and electric device of the present application will be described below with reference to the drawings as appropriate.
[0081] In one embodiment of the present application, a secondary battery is provided.
[0082] Generally, a secondary battery includes a positive electrode sheet, a negative electrode sheet, an electrolyte and a separator. During the battery charging and discharging process, active ions are embedded and released back and forth between the positive electrode sheet and the negative electrode sheet. The electrolyte plays the role of conducting ions between the positive electrode sheet and the negative electrode sheet. The separator is set between the positive electrode sheet and the negative electrode sheet, mainly to prevent the positive and negative electrodes from short-circuiting, while allowing ions to pass through.
[0083] [Positive electrode]
[0084] The positive electrode sheet includes a positive electrode current collector and a positive electrode film layer arranged on at least one surface of the positive electrode current collector, wherein the positive electrode film layer includes the positive electrode active material of the first aspect of the present application.
[0085] As an example, the positive electrode current collector has two surfaces opposite to each other in its thickness direction, and the positive electrode film layer is disposed on any one or both of the two opposite surfaces of the positive electrode current collector.
[0086] In some embodiments, the positive electrode current collector may be a metal foil or a composite current collector. For example, aluminum foil may be used as the metal foil. The composite current collector may include a polymer material base and a metal layer formed on at least one surface of the polymer material base. The composite current collector may be formed by forming a metal material (aluminum, aluminum alloy, nickel, nickel alloy, titanium, titanium alloy, silver and silver alloy, etc.) on a polymer material substrate (such as a substrate of polypropylene (PP), polyethylene terephthalate (PET), polybutylene terephthalate (PBT), polystyrene (PS), polyethylene (PE), etc.).
[0087] In some embodiments, the positive electrode film layer may further optionally include a binder. As an example, the binder may include at least one of polyvinylidene fluoride (PVDF), polytetrafluoroethylene (PTFE), vinylidene fluoride-tetrafluoroethylene-propylene terpolymer, vinylidene fluoride-hexafluoropropylene-tetrafluoroethylene terpolymer, tetrafluoroethylene-hexafluoropropylene copolymer, and fluorine-containing acrylate resin.
[0088] In some embodiments, the positive electrode film layer may further include a conductive agent, which may include, for example, at least one of superconducting carbon, acetylene black, carbon black, Ketjen black, carbon dots, carbon nanotubes, graphene, and carbon nanofibers.
[0089] In some embodiments, the positive electrode sheet can be prepared in the following manner: the components for preparing the positive electrode sheet, such as the positive electrode active material, the conductive agent, the binder and any other components are dispersed in a solvent (such as N-methylpyrrolidone) to form a positive electrode slurry; the positive electrode slurry is coated on the positive electrode collector, and after drying, cold pressing and other processes, the positive electrode sheet can be obtained.
[0090] [Negative electrode]
[0091] The negative electrode sheet includes a negative electrode current collector and a negative electrode film layer disposed on at least one surface of the negative electrode current collector, wherein the negative electrode film layer includes a negative electrode active material.
[0092] As an example, the negative electrode current collector has two surfaces opposite to each other in its thickness direction, and the negative electrode film layer is disposed on any one or both of the two opposite surfaces of the negative electrode current collector.
[0093] In some embodiments, the negative electrode current collector may be a metal foil or a composite current collector. For example, as the metal foil, copper foil may be used. The composite current collector may include a polymer material base layer and a metal layer formed on at least one surface of the polymer material substrate. The composite current collector may be formed by forming a metal material (copper, copper alloy, nickel, nickel alloy, titanium, titanium alloy, silver and silver alloy, etc.) on a polymer material substrate (such as a substrate of polypropylene (PP), polyethylene terephthalate (PET), polybutylene terephthalate (PBT), polystyrene (PS), polyethylene (PE), etc.).
[0094] In some embodiments, the negative electrode active material may adopt the negative electrode active material for the battery known in the art. As an example, the negative electrode active material may include at least one of the following materials: artificial graphite, natural graphite, soft carbon, hard carbon, silicon-based materials, tin-based materials, lithium titanate, etc. The silicon-based material may be selected from at least one of elemental silicon, silicon oxide compounds, silicon-carbon composites, silicon-nitrogen composites, and silicon alloys. The tin-based material may be selected from at least one of elemental tin, tin oxide compounds, and tin alloys. However, the present application is not limited to these materials, and other traditional materials that can be used as negative electrode active materials for batteries may also be used. These negative electrode active materials may be used alone or in combination of two or more.
[0095] In some embodiments, the negative electrode film layer may further include a binder. The binder may be selected from at least one of styrene-butadiene rubber (SBR), polyacrylic acid (PAA), sodium polyacrylate (PAAS), polyacrylamide (PAM), polyvinyl alcohol (PVA), sodium alginate (SA), polymethacrylic acid (PMAA) and carboxymethyl chitosan (CMCS).
[0096] In some embodiments, the negative electrode film layer may further include a conductive agent, which may be selected from at least one of superconducting carbon, acetylene black, carbon black, Ketjen black, carbon dots, carbon nanotubes, graphene and carbon nanofibers.
[0097] In some embodiments, the negative electrode film layer may optionally include other additives, such as a thickener (eg, sodium carboxymethyl cellulose (CMC-Na)).
[0098] In some embodiments, the negative electrode sheet can be prepared in the following manner: the components for preparing the negative electrode sheet, such as the negative electrode active material, the conductive agent, the binder and any other components are dispersed in a solvent (such as deionized water) to form a negative electrode slurry; the negative electrode slurry is coated on the negative electrode collector, and after drying, cold pressing and other processes, the negative electrode sheet can be obtained.
[0099] [Electrolytes]
[0100] The electrolyte plays the role of conducting ions between the positive electrode and the negative electrode. The present application has no specific restrictions on the type of electrolyte, which can be selected according to needs. For example, the electrolyte can be liquid, gel or all-solid.
[0101] In some embodiments, the electrolyte is an electrolyte solution, which includes an electrolyte salt and a solvent.
[0102] In some embodiments, the electrolyte salt can be selected from at least one of lithium hexafluorophosphate, lithium tetrafluoroborate, lithium perchlorate, lithium hexafluoroarsenate, lithium bis(fluorosulfonyl)imide, lithium bis(trifluoromethanesulfonyl)imide, lithium trifluoromethanesulfonate, lithium difluorophosphate, lithium difluorooxalatoborate, lithium dioxalatoborate, lithium difluorodioxalatophosphate, and lithium tetrafluorooxalatophosphate.
[0103] In some embodiments, the solvent can be selected from at least one of ethylene carbonate, propylene carbonate, ethyl methyl carbonate, diethyl carbonate, dimethyl carbonate, dipropyl carbonate, methyl propyl carbonate, ethyl propyl carbonate, butylene carbonate, fluoroethylene carbonate, methyl formate, methyl acetate, ethyl acetate, propyl acetate, methyl propionate, ethyl propionate, propyl propionate, methyl butyrate, ethyl butyrate, 1,4-butyrolactone, cyclopentane sulfone, dimethyl sulfone, methyl ethyl sulfone and diethyl sulfone.
[0104] In some embodiments, the electrolyte may further include additives, such as negative electrode film-forming additives, positive electrode film-forming additives, and additives that can improve certain battery properties, such as additives that improve battery overcharge performance, additives that improve battery high or low temperature performance, etc.
[0105] [Isolation film]
[0106] In some embodiments, the secondary battery further includes a separator. The present application has no particular limitation on the type of separator, and any known porous separator with good chemical stability and mechanical stability can be selected.
[0107] In some embodiments, the material of the isolation membrane can be selected from at least one of glass fiber, non-woven fabric, polyethylene, polypropylene and polyvinylidene fluoride. The isolation membrane can be a single-layer film or a multi-layer composite film, without particular limitation. When the isolation membrane is a multi-layer composite film, the materials of each layer can be the same or different, without particular limitation.
[0108] In some embodiments, the positive electrode sheet, the negative electrode sheet, and the separator may be formed into an electrode assembly by a winding process or a lamination process.
[0109] In some embodiments, the secondary battery may include an outer package, which may be used to encapsulate the electrode assembly and the electrolyte.
[0110] In some embodiments, the outer packaging of the secondary battery may be a hard shell, such as a hard plastic shell, an aluminum shell, a steel shell, etc. The outer packaging of the secondary battery may also be a soft package, such as a bag-type soft package. The material of the soft package may be plastic, and examples of the plastic include polypropylene, polybutylene terephthalate, and polybutylene succinate.
[0111] The present application has no particular limitation on the shape of the secondary battery, which may be cylindrical, square or any other shape. Figure 1 The secondary battery 5 is a square structure as an example.
[0112] In some embodiments, reference Figure 2 , the outer packaging may include a shell 51 and a cover plate 53. Among them, the shell 51 may include a bottom plate and a side plate connected to the bottom plate, and the bottom plate and the side plate enclose a receiving cavity. The shell 51 has an opening connected to the receiving cavity, and the cover plate 53 can be covered on the opening to close the receiving cavity. The positive electrode sheet, the negative electrode sheet and the isolation membrane can form an electrode assembly 52 through a winding process or a lamination process. The electrode assembly 52 is encapsulated in the receiving cavity. The electrolyte is infiltrated in the electrode assembly 52. The number of electrode assemblies 52 contained in the secondary battery 5 can be one or more, and those skilled in the art can select according to specific actual needs.
[0113] In some embodiments, secondary batteries may be assembled into a battery module. The number of secondary batteries contained in the battery module may be one or more, and the specific number may be selected by those skilled in the art according to the application and capacity of the battery module.
[0114] Figure 3 4 is an example of a battery module. Figure 3 In the battery module 4, the plurality of secondary batteries 5 may be arranged in sequence along the length direction of the battery module 4. Of course, they may also be arranged in any other manner. Further, the plurality of secondary batteries 5 may be fixed by fasteners.
[0115] Optionally, the battery module 4 may further include a housing having a receiving space, and the plurality of secondary batteries 5 are received in the receiving space.
[0116] In some embodiments, the battery modules described above may also be assembled into a battery pack. The battery pack may contain one or more battery modules, and the specific number may be selected by those skilled in the art according to the application and capacity of the battery pack.
[0117] Figure 4 and Figure 5 1 is a battery pack 1 as an example. Figure 4 and Figure 5 The battery pack 1 may include a battery box and a plurality of battery modules 4 disposed in the battery box. The battery box includes an upper box body 2 and a lower box body 3. The upper box body 2 can cover the lower box body 3 and form a closed space for accommodating the battery modules 4. The plurality of battery modules 4 can be arranged in the battery box in any manner.
[0118] In addition, the present application also provides an electrical device, which includes at least one of the secondary battery, battery module, or battery pack provided in the present application. The secondary battery, battery module, or battery pack can be used as a power source for the electrical device, and can also be used as an energy storage unit for the electrical device. The electrical device may include mobile devices (such as mobile phones, laptops, etc.), electric vehicles (such as pure electric vehicles, hybrid electric vehicles, plug-in hybrid electric vehicles, electric bicycles, electric scooters, electric golf carts, electric trucks, etc.), electric trains, ships and satellites, energy storage systems, etc., but are not limited thereto.
[0119] As the electrical device, a secondary battery, a battery module or a battery pack may be selected according to its usage requirements.
[0120] Figure 6 The power consumption device is taken as an example. The power consumption device is a pure electric vehicle, a hybrid electric vehicle, or a plug-in hybrid electric vehicle, etc. In order to meet the power consumption device's requirements for high power and high energy density of secondary batteries, a battery pack or a battery module can be used.
[0121] Another example of a device may be a mobile phone, a tablet computer, a notebook computer, etc. Such a device is usually required to be thin and light, and a secondary battery may be used as a power source.
[0122] Example
[0123] Hereinafter, the embodiments of the present application will be described. The embodiments described below are exemplary and are only used to explain the present application, and should not be construed as limiting the present application. If no specific techniques or conditions are indicated in the embodiments, the techniques or conditions described in the literature in this area or the product specifications are used. If the manufacturer is not indicated in the reagents or instruments used, they are all conventional products that can be obtained commercially.
[0124] Example 1
[0125] Step a: LiNi core 0.8 Co 0.1 Mn 0.1 O2, Zr(NO3)4·5H2O, Dy(NO3)4·6H2O are dispersed in deionized water.
[0126] Among them, the molar ratio of Zr(NO3)4·5H2O to Dy(NO3)4·6H2O is 8:2.
[0127] The sum of the weights of Zr(NO3)4·5H2O and Dy(NO3)4·6H2O and LiNi 0.8 Co 0.1 Mn 0.1The weight ratio of O2 is 9.876:100. After mixing evenly, the water is evaporated at 80°C and dried for 4 hours to obtain material A.
[0128] Step b: sintering material A in an air atmosphere at a first sintering temperature of 900° C. and a first sintering time of 6 hours to obtain material B having a first coating layer.
[0129] Step c: Add Zr(NO3)4·5H2O, Li3PO4 and material B into anhydrous ethanol, and add complexing agent H2C2O4.
[0130] Among them, the molar ratio of Li3PO4 to H2C2O4 is 1:2.
[0131] The molar ratio of Zr(NO3)4·5H2O to Li3PO4 is 2:3.
[0132] The weight ratio of the sum of the weight of Zr(NO3)4·5H2O and Li3PO4 to the weight of material B is 2.542:100.
[0133] After mixing evenly, stir at 80°C until the solution evaporates to dryness, and continue drying for 6 hours to obtain material C.
[0134] Step d: Place material C in air at a second sintering temperature of 200°C and sinter for a second sintering time of 5 hours, then heat to a third sintering temperature of 600°C, continue sintering for a third sintering time of 5 hours, and cool to room temperature to obtain a positive electrode active material having a first coating layer and a second coating layer.
[0135] Example 2
[0136] In addition to step c,
[0137] Except that the weight ratio of the sum of the weight of Zr(NO3)4·5H2O and Li3PO4 to material B is 2.542:100, other conditions are the same as those in Example 1.
[0138] Example 3
[0139] In addition to step 3,
[0140] Except that the weight ratio of the sum of the weight of Zr(NO3)4·5H2O and Li3PO4 to material B is 5.084:100, other conditions are the same as those in Example 1.
[0141] Example 4
[0142] Step a: LiNi core 0.8 Co 0.1 Mn 0.1 O2, Zr(NO3)4·5H2O, Yb(NO3)3·5H2O are dispersed in deionized water.
[0143] Among them, the molar ratio of Zr(NO3)4·5H2O to Yb(NO3)3·5H2O is 8:2.
[0144] The sum of the weights of Zr(NO3)4·5H2O and Yb(NO3)3·5H2O and LiNi 0.8 Co 0.1 Mn 0.1 The weight ratio of O2 is 9.420:100. After mixing evenly, stir at 80°C until the water is completely evaporated, and continue drying for 4 hours to obtain material A.
[0145] Step b: sintering material A in an air atmosphere at a first sintering temperature of 900° C. and a first sintering time of 6 hours to obtain material B having a first coating layer.
[0146] Step c: Add Zr(NO3)4·5H2O, Li3PO4 and material B into anhydrous ethanol, and add complexing agent H2C2O4.
[0147] Among them, the molar ratio of Li3PO4 to H2C2O4 is 1:2.
[0148] The molar ratio of Zr(NO3)4·5H2O to Li3PO4 is 2:3.
[0149] The molar ratio of the sum of the weights of Zr(NO3)4·5H2O and Li3PO4 to material B is 5.084:100.
[0150] After mixing evenly, stir at 80°C until the solvent is completely evaporated, and continue drying for 6 hours to obtain material C.
[0151] Step 4: Place material C in the air at a second sintering temperature of 200°C, sinter for 5 hours according to the second sintering time, then heat to a third sintering temperature of 600°C, continue sintering for 5 hours for the third sintering time, and cool to room temperature to obtain a positive electrode active material having a first coating layer and a second coating layer.
[0152] Example 5
[0153] Step a: LiNi core 0.8 Co 0.1 Mn 0.1 O2, Zr(NO3)4·5H2O, Dy(NO3)4·6H2O are dispersed in deionized water.
[0154] Among them, the molar ratio of Zr(NO3)4·5H2O to Dy(NO3)4·6H2O is 8:2.
[0155] The sum of the weight of Zr(NO3)4·5H2O and Dy(NO3)4 and LiNi 0.8 Co 0.1 Mn 0.1 The weight ratio of O2 is 9.867:100. After mixing evenly, stir at 80°C until the water is completely evaporated, and continue drying for 4 hours to obtain material A.
[0156] Step b: sintering material A in an air atmosphere at a first sintering temperature of 900° C. and a first sintering time of 6 hours to obtain material B having a first coating layer.
[0157] Step c: Add NH4H2PO4, Li2CO3 and material B into anhydrous ethanol, and add complexing agent H2C2O4.
[0158] Among them, the molar ratio of NH4H2PO4 to H2C2O4 is 1:2.
[0159] The molar ratio of NH4H2PO4 to Li2CO3 is 3:2.
[0160] The weight ratio of the sum of the weight of NH4H2PO4 and Li2CO3 to the weight of material B is 2.8377:100.
[0161] After mixing evenly, stir at 80°C until the solvent is completely evaporated, and continue drying for 6 hours to obtain material C.
[0162] Step d: placing material C in air at a second sintering temperature of 200°C and sintering for a second sintering time of 5 hours, then heating to a third sintering temperature of 600°C, continuing to sinter for a third sintering time of 5 hours, and cooling to room temperature to obtain a positive electrode active material having a first coating layer and a second coating layer.
[0163] Example 6
[0164] Step a: LiNi core 0.8 Co 0.1 Mn 0.1 O2, Zr(NO3)4·5H2O, Dy(NO3)4·6H2O are dispersed in deionized water.
[0165] Among them, the molar ratio of Zr(NO3)4·5H2O to Dy(NO3)4·6H2O is 8:2.
[0166] The sum of the weights of Zr(NO3)4·5H2O and Dy(NO3)4·6H2O and LiNi 0.8 Co 0.1 Mn 0.1 O2 weight ratio of 9.867:100, after mixing evenly, stir at 80 ° C until the water is completely evaporated to obtain material A,
[0167] Step b: sintering material A in an air atmosphere at a first sintering temperature of 900° C. and a first sintering time of 6 hours to obtain material B having a first coating layer.
[0168] Step c: Add NH4H2PO4, Li2CO3, TiO2 and material B into anhydrous ethanol, and add complexing agent H2C2O4.
[0169] Among them, the molar ratio of NH4H2PO4 to H2C2O4 is 1:2.
[0170] The molar ratio of NH4H2PO4 to Li2CO3 to TiO2 is 6:1:4.
[0171] The sum of the weight of NH4H2PO4 and Li2CO3 is equal to the weight of LiNi 0.8 Co 0.1 Mn 0.1 The weight ratio of O2 is 2.795:100. After mixing evenly, stir at 80°C until the solvent is completely evaporated, and continue drying for 6 hours to obtain material C.
[0172] Step d: placing material C in air at a second sintering temperature of 200°C for a second sintering time of 5 hours, then heating to a third sintering temperature of 600°C, continuing to sinter for 5 hours for the third sintering time, and cooling to room temperature to obtain a positive electrode active material of a first coating layer and a second coating layer.
[0173] Example 7
[0174] Step a: LiNi core 0.8 Co 0.1 Mn 0.1 O2, ZrO2, and Y2O3 are dispersed in anhydrous ethanol.
[0175] Among them, the molar ratio of ZrO2 to Y2O3 is 0.08:1.
[0176] The sum of the weight of ZrO2 and Y2O3 and LiNi 0.8 Co 0.1 Mn 0.1 The weight ratio of O2 is 3.463:100. After mixing evenly, stir at 80°C until the anhydrous ethanol is completely volatilized to obtain material A.
[0177] Step b: sintering material A in an air atmosphere at a first sintering temperature of 900° C. and a first sintering time of 6 hours to obtain material B having a first coating layer.
[0178] Step c: Add Zr(NO3)4·5H2O, Li3PO4 and material B into anhydrous ethanol, and add complexing agent H2C2O4.
[0179] Among them, the molar ratio of Li3PO4 to H2C2O4 is 1:2.
[0180] The molar ratio of Zr(NO3)4·5H2O to Li3PO4 is 2:3.
[0181] The weight ratio of the sum of the weight of Zr(NO3)4·5H2O and Li3PO4 to the weight of material B is 5.084:100.
[0182] After mixing evenly, stir at 80°C until the solvent is completely evaporated, and continue drying for 6 hours to obtain material C.
[0183] Step d: placing material C in air at a second sintering temperature of 200°C, sintering for 5 hours according to the second sintering time, then heating to a third sintering temperature of 600°C, continuing to sinter for 5 hours for the third sintering time, and cooling to room temperature to obtain a positive electrode active material having a first coating layer and a second coating layer.
[0184] Comparative Example 1
[0185] Core LiNi 0.8 Co 0.1 Mn 0.1 O2 is not treated in any way.
[0186] Comparative Example 2
[0187] Step a: LiNi core 0.8 Co 0.1 Mn 0.1 O2, Zr(NO3)4·5H2O, Dy(NO3)4·6H2O are dispersed in deionized water.
[0188] Among them, the molar ratio of Zr(NO3)4·5H2O to Dy(NO3)4·6H2O is 8:2.
[0189] The sum of the weights of Zr(NO3)4·5H2O and Dy(NO3)4·6H2O and LiNi 0.8 Co 0.1 Mn 0.1 The weight ratio of O2 is 3.292:100. After mixing evenly, stir at 80°C until the water is completely evaporated to obtain material A.
[0190] Step b: sintering material A at a first sintering temperature of 900° C. for a first sintering time of 6 hours in an air atmosphere, and cooling to room temperature to obtain a positive electrode active material.
[0191] Comparative Example 3
[0192] In addition to step a,
[0193] The sum of the weights of Zr(NO3)4·5H2O and Dy(NO3)4·6H2O and LiNi 0.8 Co 0.1 Mn 0.1 Except that the weight ratio of O2 is 6.584:100, other conditions are the same as those of Comparative Example 2.
[0194] Comparative Example 4
[0195] In addition to step a,
[0196] The sum of the weights of Zr(NO3)4·5H2O and Dy(NO3)4·6H2O and LiNi 0.8 Co 0.1 Mn 0.1 Except that the weight ratio of O2 is 9.876:100, other conditions are the same as those of Comparative Example 2.
[0197] Comparative Example 5
[0198] In addition to step a,
[0199] The sum of the weights of Zr(NO3)4·5H2O and Dy(NO3)4·6H2O and LiNi 0.8 Co 0.1 Mn 0.1 The weight ratio of O2 is 13.168:100. In step b, except that the first sintering temperature is 550°C and the first sintering time is 1.5 hours, other conditions are the same as those in Example 1.
[0200] Comparative Example 6
[0201] Step a: Zr(NO3)4·5H2O, Li3PO4, core LiNi 0.8 Co 0.1 Mn 0.1 O2 is added to anhydrous ethanol, and the complexing agent H2C2O4 is added.
[0202] Among them, the molar ratio of Zr(NO3)4·5H2O to Li3PO4 is 2:3.
[0203] The molar ratio of Li3PO4 to H2C2O4 is 1:2.
[0204] The sum of the weight of Zr(NO3)4·5H2O and Li3PO4 and LiNi 0.8 Co 0.1 Mn 0.1 The weight ratio of O2 is 2.542:100,
[0205] After mixing evenly, stir at 80°C until the solvent is completely evaporated to obtain material A.
[0206] Step b: After material A is crushed, it is placed in air at a second sintering temperature of 100°C and sintered for a second sintering time of 4 hours, then heated to a third sintering temperature of 500°C, and sintered for a further 4 hours according to the third sintering time, and cooled to room temperature to obtain a positive electrode active material having a second coating layer.
[0207] Comparative Example 7
[0208] In addition to step a,
[0209] The sum of the weight of Zr(NO3)4·5H2O and Li3PO4 and LiNi 0.8 Co 0.1 Mn 0.1 Except for the weight ratio of O2 being 5.084:100, other conditions are the same as those of Comparative Example 6.
[0210] Comparative Example 8
[0211] In addition to step a,
[0212] The sum of the weight of Zr(NO3)4·5H2O and Li3PO4 and LiNi 0.8 Co 0.1 Mn 0.1 Except that the weight ratio of O2 is 7.626:100, other conditions are the same as those of Comparative Example 6.
[0213] The relevant parameters of the positive electrode active materials of Examples 1 to 7 and Comparative Examples 1 to 8 are shown in Table 1 below.
[0214] Table 1: Parameter results of positive electrode active materials of Examples 1 to 7 and Comparative Examples 1 to 8
[0215]
[0216]
[0217] In addition, the positive electrode active materials obtained in the above Examples 1 to 7 and Comparative Examples 1 to 8 were respectively prepared into secondary batteries as shown below, and performance tests were performed. The test results are shown in Table 2 below.
[0218] (1) Preparation of secondary batteries
[0219]
Preparation of positive electrode
[0220] The positive electrode active materials in the above-mentioned embodiments and comparative examples, the conductive agent carbon black, and the binder polyvinylidene fluoride (PVDF) are dissolved in a solvent N-methylpyrrolidone (NMP) in a weight ratio of 94:3:3, and the positive electrode slurry is obtained after being fully stirred and mixed. The positive electrode slurry is then evenly coated on the positive electrode collector, and then dried, cold pressed, and cut to obtain the positive electrode sheet.
[0221]
Preparation of negative electrode sheet
[0222] The active material artificial graphite, the conductive agent carbon black, the binder styrene-butadiene rubber (SBR), and the thickener sodium hydroxymethyl cellulose (CMC) are mixed evenly in a weight ratio of 96.85:0.8:0.8:1.2, and then deionized water is added to mix evenly to prepare a negative electrode slurry; the negative electrode slurry is evenly coated on the negative electrode collector copper foil, and the negative electrode sheet is obtained after drying, cold pressing, and slitting.
[0223]
Preparation of electrolyte
[0224] In an argon atmosphere glove box (H2O<0.01ppm, O2<0.01ppm), organic solvents ethylene carbonate (EC) / ethyl methyl carbonate (EMC) were mixed evenly in a volume ratio of 4 / 6, 12.5% LiPF6 lithium salt was added and dissolved in the organic solvent, and stirred evenly to obtain an electrolyte.
[0225]
Isolation film
[0226] A polyethylene film is used as the isolation film.
[0227] The positive electrode sheet, the separator and the negative electrode sheet are stacked in order, the separator is placed between the positive and negative electrodes to play a role of isolation, and then wound to obtain a bare cell. The bare cell is placed in an outer package, the electrolyte is injected and packaged to obtain a secondary battery.
[0228] (2) Secondary battery initial gram capacity test
[0229] Each of the secondary batteries prepared above was placed in a constant temperature environment of 25°C for 5 minutes, discharged to 2.8V at 1 / 3C, and charged to 4.25V at 1 / 3C after standing for 5 minutes. Then, it was charged at a constant voltage at 4.25V to a current ≤0.05mA, and stood for 5 minutes. The charging capacity at this time was recorded as C0. Then, it was discharged to 2.8V at 1 / 3C. The discharge capacity at this time was the initial discharge capacity, recorded as D0.
[0230] The tested discharge capacity value (ie, the initial discharge capacity D0) is divided by the mass of the positive electrode active material in the secondary battery to obtain the full-electric initial gram capacity of the positive electrode active material.
[0231] (3) Secondary battery cycle performance test at 25°C
[0232] Each of the secondary batteries prepared above was charged to 4.25 V at 1C at 2.8-4.25 V in a constant temperature environment of 25°C, then charged at a constant voltage at 4.25 V to a current ≤ 0.05 mA, allowed to stand for 5 minutes, and then discharged to 2.8 V at 1C. The capacity was recorded as Dn (n = 0, 1, 2...), and the above operation was repeated for 2000 cycles to measure the capacity fading value.
[0233] (4) Secondary battery inflation performance test
[0234] Connect the above secondary batteries to the oil meter. Stand at 25℃ for 5 minutes, then discharge at 0.33C constant current to 2.8V, stand for 10 minutes, charge at constant current to 4.19V, then stand at 0.05C constant voltage for 5 minutes, charge to 97% SOC, and store at 60℃ high temperature box. The oil meter monitors the internal gas pressure of the battery cell, and when it reaches 0.4MPa, test and record the storage days.
[0235] Table 2: Performance test results of Examples 1 to 7 and Comparative Examples 1 to 8
[0236]
[0237] According to the above results, the surface of the positive electrode active material in Examples 1 to 7 is coated with a first coating layer of zirconium-based oxygen ion conductor and a second coating layer of LiM2(PO4)3. The zirconium-based oxygen ion conductor has a good complexing ability for oxygen atoms, which inhibits the oxygen generated by the irreversible reaction on the surface of the positive electrode active material particles during the charge and discharge cycle and the heat generated by the side reaction between the electrolyte, thereby improving the thermal runaway of the positive electrode active material and improving the safety performance of the secondary battery using the positive electrode active material. At the same time, the fast ion conductor has good stability and good transmission capacity for lithium ions. Therefore, the introduction of the fast ion conductor improves the kinetic properties of the positive electrode active material particles. In addition, when the thickness of the first coating layer, i.e., d1, the thickness of the second coating layer, i.e., d2, and the weight proportion of the first coating layer, A%, satisfy the above relationship, the coating layer can suppress gas production without affecting the kinetic properties of the positive electrode active material, thereby improving the cycle performance of the positive electrode active material.
[0238] In contrast, the positive electrode active material in Comparative Example 1 is not coated with the zirconium-based oxygen ion conductor and the second coating layer fast ion conductor LiM2(PO4)3, and no effective improvement is achieved in terms of cycle performance and suppression of gas production. The positive electrode active materials in Comparative Examples 2 to 5 are only coated with the zirconium-based oxygen ion conductor. Although the zirconium-based oxygen ion conductor suppresses the gas production of the positive electrode active material during the cycle, the zirconium-based oxygen ion conductor has poor conductivity to lithium ions, thus affecting the initial gram capacity of the positive electrode active material. The positive electrode active materials in Comparative Examples 6 to 8 are only coated with the fast ion conductor LiM2(PO4)3, which fails to effectively improve the gas production problem of the positive electrode active material.
[0239] It should be noted that the present application is not limited to the above-mentioned embodiments. The above-mentioned embodiments are only examples, and the embodiments having the same structure as the technical idea and exerting the same effect within the scope of the technical solution of the present application are all included in the technical scope of the present application. In addition, without departing from the scope of the main purpose of the present application, various modifications that can be thought of by those skilled in the art to the embodiments and other methods of combining some of the constituent elements in the embodiments are also included in the scope of the present application.
Claims
1. A positive electrode active material, characterized in that: It comprises a core, a first coating layer and a second coating layer, wherein the first coating layer is coated on the surface of the core, and the second coating layer is coated on the surface of the first coating layer. The core is LiNi x Co y A z O2, wherein A is Mn or Al, 0.6≤x<1, 0<y≤0.2, x+y+z=1, The first coating layer is Ln x Zr 1-x O 2-δ , 0.08<x<0.2, 0.04<δ<0.1, wherein Ln is selected from one or more of Gd, Dy, Er, Yb, and Y, The second coating layer is LiM2(PO4)3, wherein M is Ti or Zr, Relative to the total weight of the positive electrode active material, the weight proportion of the first coating layer is set to A%, the thickness of the first coating layer is set to d1, unit: nm, the thickness of the second coating layer is set to d2, unit: nm, and the positive electrode active material satisfies the following conditions: 0<d1 / (d1+d2+A)≤0.
83.
2. The positive electrode active material according to claim 1, characterized in that 0.3≤d1 / (d1+d2+A)≤0.
6.
3. The positive electrode active material according to claim 1, characterized in that The thickness of the first coating layer, ie, d1, is 2nm-35nm, and / or the thickness of the second coating layer, ie, d2, is 2nm-35nm.
4. The positive electrode active material according to any one of claims 1 to 3, characterized in that Relative to the total weight of the positive electrode active material, the weight proportion of the first coating layer is A% is 0.2%-5%, and / or, Relative to the total weight of the positive electrode active material, the weight ratio of the second coating layer is 0.2%-5%.
5. The positive electrode active material according to any one of claims 1 to 3, characterized in that The positive electrode active material has a Dv50 of 5 μm to 20 μm.
6. A method for preparing the positive electrode active material according to claim 1, characterized in that: The method comprises the steps of: mixing a Zr-containing element precursor, a Ln-containing element precursor and a LiNi x Co y A z O2 is added to deionized water, stirred at 60-80°C until the water is completely evaporated, and dried for 4-6 hours to obtain material A, wherein A is Mn or Al, 0.6≤x<1, 0<y≤0.2, x+y+z=1, and the Ln element is selected from one or more of Gd, Dy, Er, Yb, and Y; Step b: crushing the material A, placing it in an oxidizing atmosphere, and sintering it at 650-950° C. for 2-6 hours to obtain material B; Step c: dissolving lithium phosphate, a precursor containing an element M, and a complexing agent in a solvent, and then adding the material B, stirring at 60-80° C. until the solvent is completely evaporated, and continuing to dry for 4-6 hours to obtain material C, wherein M is Ti or Zr; Step d: After the material C is crushed, it is placed in an oxidizing atmosphere, first sintered at 150-250° C. for 5-10 hours, and then heated to 550-750° C. and continued to sinter for 5-15 hours to obtain the positive electrode active material.
7. The method for preparing a positive electrode active material according to claim 6, characterized in that: In the step a, the molar ratio of the Zr element-containing precursor to the Ln element-containing precursor is (4-12):1, and / or, The sum of the weight of the Zr-containing precursor and the Ln-containing precursor is equal to the weight of LiNi x Co y A z The weight ratio of O2 is (0.2-10):
100.
8. The method for preparing a positive electrode active material according to claim 6 or 7, characterized in that: In the step c, the weight ratio of the lithium phosphate salt to the precursor containing the M element is (0.5-3):1, and / or the molar ratio of the lithium phosphate salt to the complexing agent is 1:(0.6-2), and / or the weight ratio of the sum of the weight of the lithium phosphate salt and the precursor containing the M element to material B is (0.05-9):
100.
9. The method for preparing a positive electrode active material according to any one of claims 6 to 7, characterized in that: In the step a, the Zr element-containing precursor is selected from one or more of Zr(NO3)4, H2N2O7Zr, ZrOCl2, ZrOCl, and ZrO2, and the Ln element-containing precursor is selected from one or more of Gd element precursor, Dy element precursor, Er element precursor, Yb element precursor, Y element-containing precursor, and Ti element precursor.
10. The method for preparing a positive electrode active material according to claim 9, characterized in that: The Gd element-containing precursor is selected from Gd(NO3)4·6H2O, C6H 11 GdO7, and / or the Dy-containing element precursor is selected from Dy(NO3)4·6H2O, C6H 17 DYNAMIC 10 One or more of, and / or, The Er-containing element precursor is selected from Er(NO3)3·5H2O, C2H 11 One or more of ErO6, and / or, the Yb-containing element precursor is selected from Yb(NO3)3·5H2O, and / or, The Y-containing precursor is selected from Y(NO3)3·6H2O, C6H 17 O 10 One or more of Y, Y2O3, and / or, The Ti-containing element precursor is selected from one or more of TiCl4, TiOSO4, TiSO4, and tetrabutyl orthotitanate.
11. The method for preparing a positive electrode active material according to any one of claims 6 to 7, characterized in that: In step c, the lithium phosphate salt is selected from one or more of lithium phosphate and lithium dihydrogen phosphate, and / or the complexing agent is selected from one or more of oxalic acid and citric acid, and / or the solvent is selected from one or more of anhydrous ethanol, ethylene glycol, methanol or N-methylpyrrolidone.
12. The method for preparing a positive electrode active material according to any one of claims 6 to 7, characterized in that: In the step b, the oxidizing atmosphere is oxygen or air.
13. A secondary battery, characterized in that: The invention comprises the positive electrode active material according to any one of claims 1 to 5 or a positive electrode active material prepared by the method for preparing the positive electrode active material according to any one of claims 6 to 12.
14. A battery module, characterized in that: Includes the secondary battery as claimed in claim 13.
15. A battery pack, characterized in that: A battery module comprising the battery module described in claim 14.
16. An electrical device, characterized in that: The battery comprises at least one selected from the secondary battery of claim 13, the battery module of claim 14, or the battery pack of claim 15.
Citation Information
Patent Citations
Composite negative electrode active material and preparation method thereof, and lithium battery
CN109428071A
Positive electrode active material, preparation method thereof and battery containing positive electrode active material
CN110943206A